Utilización del lego mindstorms nxt 2.1 como recurso didáctico, para desarrollar el pensamiento creativo en la asignatura de ciencias naturales en los alumnos del quinto grado de la escuela de educación básica municipal Monseñor Jorge Guillermo Armijos de la ciudad de Loja - Armijos Cabrera, Martha Eugenia (2016)
This research work was carried out based on the detected problem on the lack of knowledge and training on current technology tools, and limited financial resources to acquire them; the research was to use the Lego Mindstorms NXT 2.1 as a teaching resource to develop creative thinking in children of fifth grade of the subject of Natural Sciences Education Basic Municipal School "Mons. Jorge Guillermo Armijos". The use and implementation of the Lego Mindstorms NXT 2.1 is performed according to the methodology ASSURE, each of the phases allowed the objectives to be fulfilled; this research also the scientific method, the constructivist pedagogical model and techniques used were the survey and diagnostic test for the collection of information was applied. It was found that students have difficulty learning on many issues, but the issue that more emphasis was put on the oseoatromuscular system; after developing activities and working with students proceeded to make socialization, and apply the valuation record to determine the degree of acceptance that has this teaching resource; obtaining very satisfactory results proving that this teaching resource is an important support in the development of creative thinking in children of fifth grade in the subject of Natural Sciences